A rapid method for measuring ancient coccolith size - Ruby Barrett; Ann Power; John Love; Daniela. N. Schmidt (Marine Micropaleontology, 2025)

Military-Related Weight Stigma Prospectively Predicts Dietary Restraint During Pregnancy in US Military Active-Duty Service Members: A Longitudinal Observational Study - Katherine A. Thompson; Viviana Bauman; Ruby Schrag; Marney A. White; Autumn Mains; Stephanie Rioux; Holly Spinner; Isabel Thorstad; Victoria Thomas; David Klein; Mark Haigney; Marian Tanofsky-Kraff; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

A framework for context-aware climate risk assessments - Ruby Leigh; Seth Westra; Holger R. Maier; Matthew J. Knowling; Sam Culley; Katherine A. Daniell; Ariella Helfgott; Ashley Kingsborough; Peta Brettig (Journal of Hydrology, 2025)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Integrated Body and Otolith Morphometrics Indicate a Single Stock of Bigeye Scad (Selar crumenophthalmus) in Northern Mindanao, Philippines - Renie M. Magallanes; Lhendy P. De Leon; Rosa Ruby P. Cabiguin; Emmanuel S. Delloro; Adzel Adrian G. Baldevieso; Kaent Immanuel N. Uba (Thalassas: An International Journal of Marine Sciences, 2025)

Condition Does Not Alter Responsiveness to Mating Signals in Female Pacific Field Crickets - Jon Richardson; Ruby Ales; Marlene Zuk (Journal of Insect Behavior, 2025)
Animals often vary in their condition (i.e. the amount of resources allocatable to fitness-related functions) and such variation can influence the expression of important mating behaviors like how quickly individuals respond to mating signals. If individuals in poor condition invest less in finding mates, perhaps because they can’t afford the energetic costs, then variation in condition could weaken selection on sexual signals. Conversely, if individuals in poor condition invest more in mating, say because they benefit more from finding a mate, then variation in condition could strengthen selection on sexual signals. Here we examined the effect of female condition on responsiveness to male mating signals – a key component of mating behavior – in the Pacific field cricket ( Teleogryllus oceanicus ). We manipulated female condition by rearing females on either a high- or low-quality diet. Although our diets generated substantial differences in adult body condition, the two groups of females had similar responsiveness to male mating signals. Our results suggest that, contrary to theoretical predictions, fitness-related behaviors do not always exhibit condition dependence.

Modulatory effects of bioactive natural compounds on pruritic pathways: mechanistic basis and therapeutic prospects - Wagih H. Marcus; Hassan A. Ruby; Amira E. Awwad; Mahrous H. Mahrous; Ebraheem Abouelwafa; Mohamed A. S. Badawy; Riham A. El-Shiekh; Eman S. Zaki; Mahmoud Abdelmouti Mahmoud (Inflammopharmacology, 2025)
Chronic pruritus, characterized by persistent itching, is a significant health issue that adversely affects individuals’ quality of life, particularly in palliative care environments. Conventional treatments frequently do not yield sufficient relief and may lead to undesirable side effects, which has spurred interest in exploring alternative therapeutic options. A thorough literature search was conducted across several databases such as PubMed, Web of Science, Scopus, and EKB, with an emphasis on studies involving in vitro, animal models, and clinical trials utilizing terms like “plant,” “extract,” and “pruritus.” All studies were considered regardless of their publication date and were limited to English-language articles. This review highlights the promise of various medicinal plants, including chamomile, Aloe vera , calendula, curcumin, lavender, licorice, and peppermint, as adjunctive therapies for pruritus. These plants possess a range of pharmacological properties, such as anti-inflammatory, antioxidant, and skin-soothing effects, which are relevant to the complex nature of pruritus. Their favorable safety profiles and natural origins enhance their appeal in holistic and patient-centered care models.

Exogenous Calcium Chloride and Chitosan Improved Postharvest Quality and Storability of Mango cv. ‘Mallika’ - Nishant Arya; Kumari Karuna; Ruby Rani; Abhay Mankar; Roopendra Kumar; Deepak Kumar (Applied Fruit Science, 2025)

A license to eat meat? Exploring processes underlying the effect of animal labels on meat consumption - Jessica Schiller; Matthew B. Ruby; Gudrun Sproesser (Appetite, 2025)

Detection of Neorickettsia risticii in antemortem fecal and postmortem fetal samples, with genomic insights from complete genome sequencing of a strain recovered from an aborted equine fetus - Tirth Uprety; Jacob Durazo; Litty Paul; Kemal Metiner; Rebecca Ruby; Alan Loynachan; Jennifer Janes; Laura Kenndy; Lynne Cassone; Evely Molly; Maria Quick; Jocelynn Morgan; et al. (Veterinary Microbiology, 2025)

Improving the prediction of daily reservoir releases over the CONUS using conditioned LSTM - Hoang Tran; Tian Zhou; Zeli Tan; Yilin Fang; L. Ruby Leung (Journal of Hydrology, 2025)

A Systematic Review of Potential Health Risk Assessments for Nitrate Contamination in Different Water Resources in India - Ritu Ritu; Ruby Ruby; Dimple Dimple; Nancy Nancy; Arup Giri (Water, Air, & Soil Pollution, 2025)

Exploratory Analysis of Clearance Rates and Feeding Constraints in the Invasive Black Mussel Mytella strigata (Hanley, 1843) Across Salinity and Seston Gradients - Kaent Immanuel N. Uba; Robert Keith A. Sienes; Michael H. Flores; Hessed T. Cabanilla; Gaireen D. Gaid; Junaisah Nissi L. Degoma; Delyn M. Bucay; Ruby C. Gonzales (Estuaries and Coasts, 2025)

Making the Most of Available Data: A Case Study of Converging Analyses to Model an Emerging Fishery for Jonah Crab ( Cancer borealis ) - Ruby Krasnow; Les Kaufman; Ethan Deyle (Fish and Fisheries, 2025)
Targeted fishing of Jonah crabs ( Cancer borealis ) has greatly intensified in recent decades as lobster populations have declined, forcing fishermen to shift their focus to Jonah and other crab species. Effective management of this developing fishery is limited, however, by a lack of information on their life history traits, abundance and distribution. The long‐term sustainability of the fishery depends upon near‐term efforts to maximise the value of existing data sources to assess species abundance and inform management. We applied three distinct modelling approaches—traditional linear regression, generalised additive models and empirical dynamic modelling—to data from the Maine–New Hampshire Inshore Trawl Survey to validate hypotheses about Jonah crab distribution and migration earlier derived from interviews with fishermen. There was strong agreement between the information reported by fishermen and the survey data, including depth preferences, seasonal inshore–offshore movements and sex‐specific migration patterns. This study demonstrates that rather than simply deploying a multi‐modal approach with model selection or averaging, employing a complement of statistical methods convergently and interfacing with engaged social science can better capitalise on limited fishery‐independent data to support the development of sustainable management frameworks for emerging fisheries.

Integrated assessment of biological activated carbon filters with UV/peracetic acid pretreatment for the mitigation of organic micropollutants and toxicity - Sana Ajaz; Mikaela Radke; Ashraf Aly Hassan; Prasad Kaparaju; Ruby N. Michael; Frederic D.L. Leusch (Journal of Water Process Engineering, 2025)

Shifts in functional group community diversity of threatened mesic forests with changing fire regimes - Ruby Paroissien; Ryan Tangney; Alexandria M. Thomsen; Catherine A. Offord; Mark K.J. Ooi (Forest Ecology and Management, 2025)

Direct Seeding achieves rehabilitation objectives for an operational sand mine in Southeast Queensland: A case study - Christopher D. Johnson; Matthew Thomson; Michael Vermeulen; Mark Waud; James McBroom; Ruby N. Michael (Ecological Engineering, 2025)

Two-stage Adaptive Modelling Framework for Long-term Monthly Operation of a Multi-purpose Reservoir for Regulating Environmental Flows - Ruby Jose; K. Srinivasan (Water Resources Management, 2025)

Metabarcoding reveals unique rhizospheric microbiomes of Rhizophora in Indian Mangroves - V. Kavi Sidharthan; Ruby Patel; Muthuprasad Thiyaharajan; Charishma Krishnappa; Swapnendu Pattanaik; Aundy Kumar (Folia Microbiologica, 2025)

Substrate stiffness dictates unique paths towards proliferative arrest in WI-38 cells - Alyssa M. Kaiser; Amirali Selahi; Wenjun Kong; J. Graham Ruby (GeroScience, 2025)
Finite replicative potential is a defining feature of non-transformed somatic cells, first established by Leonard Hayflick in vitro using WI-38 human lung fibroblasts. Once proliferative capacity is exhausted due to telomere shortening, cells enter into a state called replicative senescence, which can be avoided through ectopic expression of telomerase reverse transcriptase (hTERT). As WI-38 cells approach replicative arrest, molecular pathways linked to mechanotransduction are induced, including YAP signaling, but the potential interplay between replicative lifespan and the mechanical environment of the cell remains unexplored. Here, we investigate the influence of mechanosensation on the trajectory towards replicative arrest taken by WI-38 cells by growing cells on substrates of varying stiffnesses. Matrix softening slowed proliferation, altered cellular phenotypes, and shortened proliferative lifespan while hTERT expression abrogated or reduced these responses. Our analyses of bulk and single-cell RNA-sequencing and ATAC-sequencing revealed the emergence of a unique G1 transcriptional state on soft substrates, characterized by an AP-1 transcription factor program, which failed to manifest with hTERT expression. Together, these findings reveal how the mechanical environment alters WI-38 cell proliferative lifespan and dictates unique paths towards growth arrest.

Response to Article Commentary by Ranjana Sah and colleagues - Lisa C. Ruby; Stefan F. Weber; Tom Heller; Kavitha Saravu; Sabine Bélard (Infectious Diseases, 2025)

Accuracy of extended point-of-care lung ultrasound (EPLUS) for aetiological differentiation of lower respiratory tract infections: a prospective cohort study from India - Lisa C. Ruby; Stefan F. Weber; Rajagopal Kadavigere; Raviraj Vedavyasa Acharya; Rahul Magazine; Barkur Ananthakrishna Shastry; Sowmya Joylin; Ayten Sultanli; Tom Heller; Kavitha Saravu; Sabine Bélard (Infectious Diseases, 2025)

Have popular ready meals become more obesogenic? Little change in energy density and carbohydrate-to-fat ratio over a 15-year period - Ruby L. Pallon; Jeffrey M. Brunstrom; Annika N. Flynn; Callum McBride (Appetite, 2025)

Heterostructure La0.5Sr0.5Fe0.4Mn0.6O3/TiC/porous graphene oxide for efficient trace-level detection of methiocarb pesticide in environmental samples - Francis Packiaraj Don Disouza; Shen-Ming Chen; Michael Ruby Raj; So-Qian Ching; Matar Alsalwi; Prabhakarn Arunachalam; Chelladurai Karuppiah (Process Safety and Environmental Protection, 2025)

CircRNA-miRNA-mRNA interactome analysis to explore potential pathogenesis of ovarian cancer - Ruby Srivastava (Next Research, 2025)

Local amphibious cuisine: Toward the rediscovery of the gastronomic traditions of the palafito town of buenavista, Cienaga Grande Santa Marta, Colombia - Ana Ruby Correa; Aycardo Robayo; Fabián Andrés Llano; Alexander Niño Soto (International Journal of Gastronomy and Food Science, 2025)

Effect of temperature, and immersion time on the inhibition performance of Q235 steel using spent coffee grounds derived carbon quantum dots: Electrochemical, spectroscopic and surface studies - Ruby Aslam; Qihui Wang; Jeenat Aslam; Mohammad Mobin; Chaudhery Mustansar Hussain; Zhitao Yan (Biomass and Bioenergy, 2025)

Alkyl Chain-Tuned Fluorescent Sensors: Phenanthroimidazole Derivatives for Selective Detection of Nitroaromatic Compounds Containing Phenolic Group - Mohd Tameem; Abid Ali; Ruby Ahmed; Farman Ali; Nagmajahan; Musheer Ahmad (Journal of Fluorescence, 2025)

Long-term glyphosate application and its effects on soil total nitrogen and microbial composition two years after application stopped in biochar-amended soil - Negar Omidvar; Zhihong Xu; Steven M. Ogbourne; Rebecca Ford; Prabhakaran Thanjavur Sambasivam; Trong D. Tran; Babak Salehin; Ruby N. Michael; Fang Wang; Iman Tahmasbian; Rachele S. Wilson; Shahla Hosseini Bai (Applied Soil Ecology, 2025)

Suitability of the Himalayan water quality for domestic and irrigation use: A systematic review and meta-analysis - Ruby Ruby; Dimple Dimple; Arup Giri (Chemosphere, 2025)

Perfluoroalkyl and polyfluoroalkyl substances interact with platelet glycoprotein Ibα and exacerbate thrombosis - Ming Liu; Weiqing Zhao; Chaoyu Ma; Muhammad Awais; Xue Chen; Yiting Feng; Tianyu Wang; Shaoyun Zhou; Yan Bai; Shuai Jiang; Dachuan Zhang; Guangheng Zhu; et al. (Journal of Hazardous Materials, 2025)

Air pollution exposures and adverse childhood experiences in relation to sleep health in middle childhood - Jonika B. Hash; Logan C. Dearborn; Christine T. Loftus; Catherine J. Karr; Adam A. Szpiro; Emily S. Barrett; Kaja Z. LeWinn; Ruby Nguyen; Paul E. Moore; Brent Collett; Amanda N. Noroña-Zhou; Nicole R. Bush; et al. (International Journal of Hygiene and Environmental Health, 2025)

Quantitative assessment of microplastics in fish from the Gulf of Guinea, Ghana, using LDIR spectroscopy: Implications for marine food safety and health risk evaluation - Pennante Bruce-Vanderpuije; Ruby Asmah; Miriam Ameworwor; Divine Worlanyo Hotor; Lars Hildebrandt; Daniel Pröfrock; Ralf Ebinghaus; Haruna Zaid; Ishmael Cudjoe Norvimagbe; Kwadwo Ansong Asante; Abigail Akuetteh Nunoo; Mike Yaw Osei-Atweneboana (Environmental Pollution, 2025)

Two-Hour Sea Level Oscillations in Halifax Harbour - Dan Kelley; Clark Richards; Ruby Yee; Alex Hay; Knut Klingbeil; Phillip MacAulay; Ruth Musgrave (Journal of Marine Science and Engineering, 2025)
Halifax Harbour, a major seaport in Nova Scotia that is approximately 100 km southeast of the Bay of Fundy, comprises a deep inner region called Bedford Basin, connected to the adjacent ocean by a shallow channel called The Narrows. A study of sea level and currents reveals the presence of episodic oscillations in The Narrows, with a period of approximately 2 h. The oscillation strength varies from day to day and, to some extent, through the seasons. The median amplitude of the associated sea level variation is 18% that of the de-tided signal, rising to 32% at the 95-th percentile. Values this large may be of concern for the transit of deep-draft vessels through shallow parts of the harbour and for the clearance of tall vessels under the two bridges that span The Narrows. Another concerning issue is the matter of oscillations being superimposed on storm surges. In addition to such direct effects of sea level variation, shear associated with the oscillations may increase the turbulent mixing in the region, affecting the overall state of this estuarine system. We explore the nature of the oscillations as a first step towards the improvement of prediction schemes for sea level and currents in the region. This involves an analysis of the oscillations in the context of seiche and Helmholtz resonance theories and the use of a 2D numerical model to handle realistic bathymetric conditions and other complications that the simpler theories cannot address. We conclude that the predictions of Helmholtz resonance theory are in reasonable agreement with both the observations and the predictions of the numerical model.

Characterization of a silver nanoparticle derived from the fruit peel of Myristica fragrans on mosquito control - Varghese Edwin Hillary; Murugeswaran Dayana Senthamarai; Thomas Jose Antony; Stanislaus Antony Ceasar; Muthuswami Ruby Rajan; Karthikeyan Jagannathan; Heba Talat Ebeed; Savarimuthu Ignacimuthu (International Journal of Tropical Insect Science, 2025)

Non-traditional socio-environmental and geospatial determinants of Alzheimer's disease-related dementia mortality - Skanda Moorthy; Jean-Eudes Dazard; Zhuo Chen; Ruby Charak; Shruthika Palanivel; Salil Deo; Sadeer G. Al-Kindi; Sanjay Rajagopalan (Science of The Total Environment, 2025)

Electrochemical profiling of bendiocarb residues in food matrices using an interfacially engineered halloysite-ternary hydroxide hybrid - Santhiyagu Sahayaraj Rex Shanlee; Chandini Ragumoorthy; Shen-Ming Chen; Pichai Christina Ruby Stella (Process Safety and Environmental Protection, 2025)

Variation in hibernation patterns of a temperate zone mammal - Katie Crawford; Ruby Orsman; Laura Parry; Thomas O'Hagan; Julia Nowack (Journal of Thermal Biology, 2025)

Development and Preliminary Evaluation of a Food Literacy Measure for Use With Young People in Canada - Tracey Borland; Michael D.T. Fung; Emily Taylor; Michael Chaiton; Robert Schwartz; Heather Thomas; Elsie Azevedo Perry; H. Ruby Samra; Lucy Valleau; Sharon I. Kirkpatrick (Journal of the Academy of Nutrition and Dietetics, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Exposure to polyoxyethylene tallow amines (POEAs), glyphosate co-formulation surfactants, in a US pregnant population and their potential endocrine disrupting effects - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Shirisha Yelamanchili; Emily S. Barrett; Ruby H.N. Nguyen; Sheela Sathyanarayana; Shanna H. Swan; Syam S. Andra; Jia Chen (Environmental Pollution, 2025)

Correction to: Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

Assessing wheat responses to soil acidification and liming using hyperspectral imaging - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Huajian Liu; Nathaniel Jewell; Christoper J. Brien; Luke M. Mosley (Plant and Soil, 2025)

Rapid root development in clay subsoils enhances the early growth of native grassland species - Katherine Horsfall; Nicholas S. G. Williams; Ruby N. Michael; Stephen J. Livesley (Plant and Soil, 2025)

What Kills Mature Street and Park Trees in Cities? Systematic Quantitative Review of Published Case Studies - Anna Petrova; Ruby Naomi Michael; Chris Pratt (Environmental Management, 2025)
Street and park trees often endure harsher conditions, including increased temperatures and drier soil and air, than those found in urban or natural forests. These conditions can lead to shorter lifespans and a greater vulnerability to dieback. This literature review aimed to identify confirmed causes of street and park tree dieback in urban areas from around the world. Peer-reviewed case studies related to urban tree decline were scanned for the words “urban”, “city”, “cities”, “tree*”, “decline”, “dieback”, “mortality”, and “survival”. From an initial pool of 1281 papers on Web of Science and 1489 on Scopus, 65 original peer-reviewed research papers were selected for detailed analysis. Out of all species reported to decline, 46 were native, while non-natives were represented by 35 species. The most commonly affected trees were Platanus, Fraxinus, Acer, and Ficus . Most studies were conducted in Mediterranean, humid subtropical, and humid continental climates, with the greatest representation from the United States, followed by Australia, Brazil, Iran, Italy, and Russia. Many authors focused on either biotic or abiotic causes of dieback; some explored both, and some also discussed underlying environmental and urban stresses as potential predisposing factors. The majority (81% of the papers) concluded that a decline was caused by either an arthropod or a microorganism. Overall, it was suggested that changing management strategies to improve water availability and soil health might help with tree resilience. Additionally, regular monitoring and research, along with improving tree species selection and implementing biological and chemical control methods, can help prevent or slow down tree decline. Increasing awareness and adopting preventative approaches could help to extend the lifespan of street and park trees in urban environments and mitigate some of the biological threats, especially considering the challenges we may be facing due to the changing climate.

Improved Simulation of East Asian Summer Monsoon in the High-resolution CESM1 and Its Causes - Yingshuo Xiang; Lu Dong; Fengfei Song; Lixin Wu; L. Ruby Leung; Shengpeng Wang; Enze Dong; Hong Wang (Advances in Atmospheric Sciences, 2025)

Climate‐Driven Warming Disrupts the Symbiosis of Bobtail Squid Euprymna scolopes and the Luminous Bacterium Vibrio fischeri - Eve Otjacques; Brandon Jatico; Tiago A. Marques; José C. Xavier; Edward Ruby; Margaret McFall‐Ngai; Rui Rosa (Global Change Biology, 2025)
Under the current climate crisis, marine heatwaves (MHW) are expected to intensify and become more frequent in the future, leading to adverse effects on marine life. Here, we aimed to investigate the impact of environmental warming on the symbiotic relationship between the Hawaiian bobtail squid ( Euprymna scolopes ) and the bioluminescent bacterium Vibrio fischeri . We exposed eggs of E. scolopes to three different temperatures during embryogenesis, namely: (i) 25°C (yearly average), (ii) 27°C (summer maximum) or (iii) 30°C (category IV MHW), followed by a colonisation assay under the same conditions. Decreased hatching success and reduced developmental time were observed across warmer conditions compared to 25°C. Moreover, exposure to the category IV MHW led to a significant decrease in survival after 48 h. With increasing temperature, bobtail squids required more bacteria in the surrounding seawater for successful colonisation. When colonised, the regression of the light organ's appendages was not dependent on temperature, but the opposite was found in non‐colonised bobtail squids. Furthermore, the capacity for crypt 3 formation in the squid's light organ, which is crucial for enhancing resilience under stress, also declined with warming conditions. This study emphasises the critical need to study the dynamics of microbial symbiosis under the projected conditions for the ocean of tomorrow.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Physicochemical characterisation of biochar derived from sargassum spp. and its antibacterial activity - Carlos Hernández-Calderón; B. Escobar; Ruby Valdez-Ojeda; Ana Arroyo-Herrera; Tanit Toledano-Thompson; José Baas-López (Natural Product Research, 2025)

Microplastics in the lower Volta Basin, Ghana - Quantitation and fish dietary exposure assessment using advanced spectroscopic techniques - Pennante Bruce-Vanderpuije; Yaa Asabea Agadzi; Ishmael Cudjoe Norvimagbe; Ruby Asmah; Lars Hildebrandt; Daniel Pröfrock; Ralf Ebinghaus; Kwadwo Ansong Asante (Chemosphere, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Exploring soil pedogenesis through frequency-dependent magnetic susceptibility in varied lithological environments - Abdessalam Ouallali; Naima Bouhsane; Saidati Bouhlassa; Velibor Spalevic; Shuraik Kader; Ruby Michael; Paul Sestras (Euro-Mediterranean Journal for Environmental Integration, 2025)
The use of percent frequency-dependent magnetic susceptibility (χfd%) is well-established for detecting superparamagnetic (SP) components in fine-grained soils and sediments. This study employs χfd% as a direct indicator of pedogenetic processes in soils from the Moroccan Rif region. Three soil transects (T1, T2, and T3), each comprising four soil cores with depths reaching 100 to 120 cm, were sampled from distinct lithological formations within an area subject to moderate to intense erosion. A total of 272 soil samples were collected and analyzed using MS2 Bartington Instruments, providing values to calculate χfd% and identify ultrafine ferrimagnetic minerals (SP, < 0.03 μm). In Quaternary fluvial terraces (T1) soils, approximately 60% of the samples indicate a mixture of SP, multidomain (MD), and Single Stable Domain (SSD) magnetic grains, while 30% contained coarser MD grains. Only 10% of the samples exhibit predominantly superparamagnetic (SP) grains. Soils on marly substrates (T2) showed 90% of samples with a combination of SP, MD, and SSD, and just 10% had SP grains. In contrast, soils from Villafranchian sandy deposits displayed χfd% values exceeding 10% in over 50% of samples, indicating that almost all iron components consist of SP grains. Physico-chemical analyses of the soils in profiles T1, T2, and T3 reveal distinct characteristics, including variations in clay content, organic matter, nutrient levels, and proportions of free and total iron. These results are important for understanding soil evolution and pedogenesis, with profiles T1 and T3 showing advanced development marked by high mineral iron, clay, and organic matter content. In contrast, profile T2 reflects a weak stage, influencing nutrient availability and contributing to overall soil dynamics in the respective profiles. The results of this study suggest that magnetic susceptibilities in these samples primarily originate from pedogenetic sources, revealing significantly advanced pedogenesis compared to T1 and T2 soils. The findings of this study align with previous research on soil erosion and degradation in the region, demonstrating that soils developed on terraces and marly substrates are more degraded and less stable than those on sandy substrates. This study underscores the utility of magnetic susceptibility as a rapid and effective indicator for initial soil assessment and gauging the degree of pedogenesis.

Projections of future climate for U.S. national assessments: past, present, future - Samantha Basile; Allison Crimmins; Fredric Lipschultz; Kenneth E. Kunkel; Kate Marvel; Adam Terando; Claudia Tebaldi; David Pierce; Wenying Su; L. Ruby Leung; Katharine Hayhoe (Climatic Change, 2025)

Mercury toxicity resulting from enzyme alterations- minireview - Ruby A. Ynalvez; Rene A. Rangel; Jose A. Gutierrez (BioMetals, 2025)

Tundra Vegetation Community Type, Not Microclimate, Controls Asynchrony of Above‐ and Below‐Ground Phenology - Elise C. Gallois; Isla H. Myers‐Smith; Colleen M. Iversen; Verity G. Salmon; Laura L. Turner; Ruby An; Sarah C. Elmendorf; Courtney G. Collins; Madelaine J. R. Anderson; Amanda Young; Lisa Pilkinton; Gesche Blume‐Werry; et al. (Global Change Biology, 2025)
The below‐ground growing season often extends beyond the above‐ground growing season in tundra ecosystems and as the climate warms, shifts in growing seasons are expected. However, we do not yet know to what extent, when and where asynchrony in above‐ and below‐ground phenology occurs and whether variation is driven by local vegetation communities or spatial variation in microclimate. Here, we combined above‐ and below‐ground plant phenology metrics to compare the relative timings and magnitudes of leaf and fine‐root growth and senescence across microclimates and plant communities at five sites across the Arctic and alpine tundra biome. We observed asynchronous growth between above‐ and below‐ground plant tissue, with the below‐ground season extending up to 74% (~56 days) beyond the onset of above‐ground leaf senescence. Plant community type, rather than microclimate, was a key factor controlling the timing, productivity, and growth rates of fine roots, with graminoid roots exhibiting a distinct ‘pulse’ of growth later into the growing season than shrub roots. Our findings indicate the potential of vegetation change to influence below‐ground carbon storage as the climate warms and roots remain active in unfrozen soils for longer. Taken together, our findings of increased root growth in soils that remain thawed later into the growing season, in combination with ongoing tundra vegetation change including increased shrub and graminoid abundance, indicate increased below‐ground productivity and altered carbon cycling in the tundra biome.

Incorporating citizen science into IUCN Red List assessments - Rachael Gallagher; Erin Roger; Jasmin Packer; Cameron Slatyer; Jodi Rowley; Will Cornwell; Emilie Ens; Sarah Legge; Colin Simpfendorfer; Ruby Stephens; Thomas Mesaglio (Conservation Biology, 2025)
Many citizen scientists are highly motivated to help address the current extinction crisis. Their work is making valuable contributions to protecting species by raising awareness, identifying species occurrences, assessing population trends, and informing direct management actions, such as captive breeding. However, clear guidance is lacking about how to use existing citizen science data sets and how to design effective citizen science programs that directly inform extinction risk assessments and resulting conservation actions based on the International Union for Conservation of Nature (IUCN) Red List criteria. This may be because of a mismatch between what citizen science can deliver to address extinction risk and the reality of what is needed to inform threatened species listing based on IUCN criteria. To overcome this problem, we examined each IUCN Red List criterion (A–E) relative to the five major types of citizen science outputs relevant to IUCN assessments (occurrence data, presence–absence observations, structured surveys, physical samples, and narratives) to recommend which outputs are most suited to use when applying the IUCN extinction risk assessment process. We explored real‐world examples of citizen science projects on amphibians and fungi that have delivered valuable data and knowledge for IUCN assessments. We found that although occurrence data are routinely used in the assessment process, simply adding more observations of occurrence from citizen science information may not be as valuable as inclusion of more nuanced data types, such as presence–absence data or information on threats from structured surveys. We then explored the characteristics of citizen science projects that have already delivered valuable data to support assessments. These projects were led by recognized experts who champion and validate citizen science data, thereby giving greater confidence in its accuracy. We urge increased recognition of the value of citizen science data within the assessment process.

Reuse of consumer products: Climate account and rebound effects potential - Ruby Bubinek; Ursula Knaack; Ciprian Cimpan (Sustainable Production and Consumption, 2025)

Classic Theory of Aerosol Filtration for Application to Urban Green Infrastructure - Nathalie Tomson; Ruby N. Michael; Igor E. Agranovski (Water, Air, & Soil Pollution, 2025)
The use of green infrastructure (GI) in urban environments has been widely investigated for its associated ecosystem services including air pollution mitigation. Plants are well-known for their ability of purifying air through photosynthesis and microbial activities occurring in the rhizosphere, however the simple filtration of particulate matter in air by plants is still not well understood. This study aimed to investigate the potential to adapt classic filtration theory for application in GI design. Two native Australian plants used as filter media were involved in laboratory experiments to remove aerosol particles ranging in size from 0.3 to > 10 µm. A comparison of aerosol removal efficiencies obtained from the laboratory experiments and predicted through classic filtration theory showed good correlation for the smaller (needle-like) leaf system. In contrast, the correlation obtained for a plant with larger elliptical leaves was not as good, showing a larger difference between the results. Such outcomes led to the conclusion that smaller and spatially homogeneous plant systems have more predictable aerosol filtration characteristics, which can be reasonably calculated using filtration theory. This finding provides practical insight into GI design, allowing quantitative predictions of local air pollution reductions using green barriers. Graphical Abstract

Theoretical studies on safety and efficacy of 16 small-molecule MC4R antagonists as therapeutics for obesity - Sravani Joshi; Ruby Srivastava (Journal of Proteins and Proteomics, 2025)

Peptide-Based Nanoparticles from Agricultural and Food Waste: Applications in Smart Food Packaging - Pooja yadav; Nishita Makkar; Muskan Jain; Ruby Prakash (International Journal of Peptide Research and Therapeutics, 2025)

Implications of scale up flexible plastic packaging recycling in the United States - Michael Severson; Tessa Lee; Yuan-Yuan Lee; Sameer Kulkarni; Ruby Nguyen (Waste Management, 2025)

Why ecologists struggle to predict coexistence from functional traits - Jacob I. Levine; Ruby An; Nathan J.B. Kraft; Stephen W. Pacala; Jonathan M. Levine (Trends in Ecology & Evolution, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Isotopic niche dynamics in populations of facultative amphidromous fish - Rodrigo Ramírez-Álvarez; Sergio Contreras; Ruby López-Rodríguez; Konrad Górski (Hydrobiologia, 2025)

Multi-Objective Modeling Framework for Environmental Flow Optimization in a River-Reservoir System Using Histogram Comparison Approach for Estimation of Hydrologic Alteration - Ruby Jose; Srinivasan K (Water Resources Management, 2025)

Benefits and burdens: perceiving the impact of non-indigenous black mussel (Mytella strigata) on ecosystem services and human well-being in Panguil Bay, Philippines - Kaent Immanuel N. Uba; Robert Keith A. Sienes; Hessed T. Cabanilla; Paz Geneveve Q. Gacus; Michael H. Flores; Ruby C. Gonzales; Junaisah Nissi L. Degoma; Delyn M. Bucay (Biological Invasions, 2025)